Measurement Controls in Anomalies Research - Dibble, Jr., Walter E.; Tiller, William A. (Journal of Scientific Exploration, 2011)
Members of the Society for Scientific Exploration have expressed considerable concern regarding proper control measures in research of anomalies (subtle energy research, etc.). This is quite proper and deserves some comment from us since the topic applies so well to the work we are conducting in “conditioned spaces.” Also, the need by researchers for good “anomaly detectors” is paramount and is intimately connected to the search for good controls. Both issues are addressed in this communication.